2011
DOI: 10.1093/toxsci/kfr306
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivation versus Detoxication of the Urothelial Carcinogen Aristolochic Acid I by Human Cytochrome P450 1A1 and 1A2

Abstract: Exposure to aristolochic acid (AA) is associated with human nephropathy and urothelial cancer. Individual susceptibility to AA-induced disease likely reflects individual differences in enzymes that metabolize AA. Herein, we evaluated AAI metabolism by human cytochrome P450 (CYP) 1A1 and 1A2 in two CYP1A-humanized mouse lines that carry functional human CYP1A1 and CYP1A2 genes in the absence of the mouse Cyp1a1/1a2 orthologs. Human and mouse hepatic microsomes and human CYPs were also studied. Human CYP1A1 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
93
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(102 citation statements)
references
References 37 publications
9
93
0
Order By: Relevance
“…Groups male mice ( n  = 4; 8–10 weeks of age) were used throughout the study. WT, hSULT1A1/2 , Sult1a1(−/−) and Sult1d1(−/−) mice were treated with a single dose of 50 mg/kg body weight AAI or AAII by oral gavage according to treatment protocols used previously to study AA metabolism (Arlt et al 2011; Levova et al 2011; Stiborova et al 2012). AAI and AAII (as sodium salts) were dissolved in water at a concentration of 5 mg/mL.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Groups male mice ( n  = 4; 8–10 weeks of age) were used throughout the study. WT, hSULT1A1/2 , Sult1a1(−/−) and Sult1d1(−/−) mice were treated with a single dose of 50 mg/kg body weight AAI or AAII by oral gavage according to treatment protocols used previously to study AA metabolism (Arlt et al 2011; Levova et al 2011; Stiborova et al 2012). AAI and AAII (as sodium salts) were dissolved in water at a concentration of 5 mg/mL.…”
Section: Methodsmentioning
confidence: 99%
“…1a) (Stiborova et al 2013, 2014a). Several human enzymes capable of activating AA by nitroreduction have been identified and include cytosolic NAD(P)H:quinone oxidoreductase (NQO1) (Stiborova et al 2002, 2003), and microsomal enzymes including cytochrome P450 (CYP) 1A1, CYP1A2 and NADPH:CYP oxidoreductase (Arlt et al 2011, 2015a; Stiborova et al 2001a, 2005, 2012). It has been shown that both AAI and AAII exert their genotoxic and carcinogenic properties by DNA adduct formation and that reductive metabolic activation is a prerequisite for generation of DNA adducts in vivo and in vitro (Gokmen et al 2013; Schmeiser et al 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The toxic mechanism of AAI, especially the P450-mediated AAI metabolic activation, has been extensively investigated (Chan et al, 2007;Levova et al, 2011;Stiborova et al, 2012). The metabolism profile of AAI was clearly reported (Stiborova et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the metabolism of AA have reported the involvement of several enzymes that catalyze the reduction reactions resulting in bioactivation of AA [25,29]. The most important of these enzymes include cytosolic nicotinamide adenine dinucleotide phosphate (NADPH):quinone oxidoreductase 1 (NQO1), microsomal cytochrome P450 (CYP) mainly 1A1, CYP1A2, renal microsome NADPH:CYP oxidoreductase (POR), and prostaglandin H synthase [25,30,31].…”
Section: Enzymatic Metabolization Of Aa Leading To the Formation Of Dmentioning
confidence: 99%